Institutional determinants of social inequality - Frederique Autin (Frontiers Research Topics, 2016)
Understanding the factors that create and maintain social inequalities is a core question in social psychology. Research has so far mainly focused on the role of individual stereotyping, prejudice and discrimination. However, there is growing evidence that, beyond the "biased" acts of prejudiced individuals, structural factors related to the very functioning of institutions and organizations can play a role in the reproduction of social inequalities. Indeed, in industrialized countries, society is structured in a way that reflects the perspective of, is organized by, and benefits the dominant groups. In this Research Topic, we propose to bring together researchers who study how institutional ideologies and practices promote norms, rules and opportunities that favor dominant groups and disadvantage dominated groups. This question can be tackled by work investigating how institutional practices (e.g., grading, tracking, recruitment, ...) and ideologies (e.g., meritocracy, individualism, protestant work ethic, ...) shape the psychological experience of (dis)advantaged people. Moreover, another interesting venue is represented by work investigating how the institutional practices and ideologies are enacted by the agents (e.g., teachers, recruiters, leaders, ...). Taking the perspective of agents allows to investigate how institutional functioning constrains the actual opportunities they provide to (dis)advantaged individuals. This could also highlight how institutional ideologies and practices are incorporated by agents, thus revealing mechanisms of change vs. perpetuation of the institutional functioning.